2012
DOI: 10.3892/mmr.2012.919
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the IHC, FISH, SISH and qPCR methods for the molecular diagnosis of breast cancer

Abstract: Abstract. Her2 proto-oncogene amplification and protein overexpression is observed in 20-40% of patients with breast cancer and plays a crucial role in invasive breast cancer and its treatment. In the present study, we investigated samples from 131 patients with invasive breast carcinoma. In all cases, the overexpression/amplification level of Her2 was determined using manual immunohistochemistry (IHC) and/or automatic IHC, fluorescence in situ hybridization (FISH), silver in situ hybridization (SISH) and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Furthermore, qPCR has been demonstrated to be a valuable tool for the evalu ation of HER2 gene amplification. These results are similar to those of a previous extensive and multicentric study focusing on the comparison of various ISH methods and qPCR in breast cancer, as well as being comparable with a previous study on breast carcinoma (10,26).…”
Section: Values -----------------------------------------------------supporting
confidence: 93%
“…Furthermore, qPCR has been demonstrated to be a valuable tool for the evalu ation of HER2 gene amplification. These results are similar to those of a previous extensive and multicentric study focusing on the comparison of various ISH methods and qPCR in breast cancer, as well as being comparable with a previous study on breast carcinoma (10,26).…”
Section: Values -----------------------------------------------------supporting
confidence: 93%
“…neoadjuvant therapy), which might influence the regulation and activity of the PI3K signalling pathway (Gonzalez-Angulo et al 2011). Third, while most other studies used IHC (Perren et al 1999; Depowski et al 2001; Lin et al 2003; Lee et al 2004; Engin et al 2006; Aleskandarany et al 2010; Gonzalez-Angulo et al 2011), we used qPCR to determine expression of PTEN and PIK3CA, which enables quantification relative to a household gene and is not biased by subjective factors such as the experience of the assessor (Tvrdik et al 2012; Mendoza et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…As few as 50 cells extracted from archival formalin-fixed paraffin-embedded (FFPE) tissues may be quantified using quantitative PCR (qPCR) [9] , [10] . The results from qPCR of HER2 measurements have been positively correlated with the results from IHC and FISH analysis [10] , [11] , [12] , [13] . Koudelakova et al compared qPCR to IHC and FISH data in breast cancer samples, and found that high sensitivity and specificity of the new method was achieved and the results obtained with the qPCR method and FISH/IHC agreed [14] .…”
Section: Introductionmentioning
confidence: 99%